Strategy Committees on European Public Boards: Characteristics and Tasks - Małgorzata Kuczara (European Management Studies)
Purpose: Despite the extensive debate over the years about the involvement of boards in strategy, little is known about special committees dedicated to strategy. This paper aims to enhance understanding of strategy committees (SCs) within European public boards by addressing two key questions: What are the characteristics of SCs, and what tasks do they undertake? Design/Methodology/Approach: Document analysis from 81 SCs established by boards of directors and supervisory boards in companies listed on nine major European stock exchanges. Findings: We find that SCs predominantly focus on tasks aligned with the board’s strategic role. These tasks involve shaping the content, context, and implementation of the strategy, as well as influencing strategic decisions. Furthermore, SCs actively engage in strategic control at both the company and decision/ activity levels. They engage in tasks that are closely tied to the advising role of the board rooted in resource-based theories and the control role within the strategic domain that emerges from agency theory. Research Limitations/Implications: Using publicly available corporate documents introduces potential biases, as companies selectively disclose information while legally obligated to publish annual reports. The voluntary nature of revealing information about SCs implies that reported characteristics and tasks may not fully represent the actual state. Originality/Value: It is the first study to explore SCs in various European countries by showing their scale, structures, compositions and especially the tasks they declare and handle.